Measuring, modelling and testing ozone exposure, flux and effects on vegetation in southern European conditions--what does not work? A review from Italy. - Ferretti, M; Fagnano, M; Amoriello, T; Badiani, M; Ballarin-Denti, A; Buffoni, A; Bussotti, F; Castagna, A; Cieslik, S; Costantini, A; De Marco, A; Gerosa, G; et al. (Environmental pollution (Barking, Essex : 1987), 2007)
Ozone (O3) exposure at Italian background sites exceeds UN/ECE concentration-based critical levels (CLe(c)), if expressed in terms of AOT40. Yet the occurrence of adverse effects of O3 on forests and crops is controversial. Possible reasons include (i) ability of response indicators to provide an unbiased estimate of O3 effects, (ii) setting of current CLe(c) in terms of cut-off value and accumulation level, (iii) response functions adopted to infer a critical level, (iv) environmental limitation to O3 uptake and (v) inherent characteristics of Mediterranean vegetation. In particular, the two latter points suggest that critical levels based on accumulated stomatal flux (CLe(f)) can be a better predictor of O3 risk than CLe(c). While this concept is largely acknowledged, a number of factors may limit its applicability for routine monitoring. This paper reviews levels, uptake and vegetation response to O3 in Italy over recent years to discuss value, uncertainty and feasibility of different approaches to risk assessment.
Keywords: AOTx; Critical levels; Effects; Mediterranean Region; Ozone; Stomatal flux

Short-term changes of response indicators of ecosystem status in broadleaved forests in Tuscany (central Italy) - Ferretti, M; Bonini, I; Bussotti, F; Celesti, C; Cenni, E; Chiarucci, A; Cozzi, A; De Dominicis, V; Grossoni, P; Leonzio, C (WATER AIR AND SOIL POLLUTION, 1999)
The status of different response indicators of forest condition were measured and assessed between 1995 and 1997 at 6 Permanent Monitoring Plots (PMPs) in Tuscany (central Italy), where beech, holm oak and Turkey oak are the most frequent tree species. Foliage transparency, leaf damage and crown dieback have changed significantly over the monitoring period. Leaf area, length of the current year shoots, and total leaf area changed as well, but only for Turkey oak. Changes were consistent between and within the plots. Different indices of plant diversity showed marked changes, apparently linked to natural dynamics within individual ecosystems. These rapid and contrasting fluctuations in the various indicators of forest ecosystem make it difficult to derive a synthesis about the general condition of ecosystems and - especially - about the effects of air pollution.
Keywords: Biodiversity; crown condition; crown productivity; forest health; long-term monitoring; Permanent plots; response indicators

Air pollution, forest condition and forest decline in Southern Europe: an overview. - Bussotti, F; Ferretti, M (Environmental pollution (Barking, Essex : 1987), 1998)
Over the last decades much of the work on the impact of air pollution on forests in Europe has concentrated on central and northern countries. The southern part of Europe has received far less attention, although air pollutants-especially the photochemical ones-can reach concentrations likely to have adverse effects on forest vegetation. Although international forest condition surveys present serious problems where data consistency is concerned, they reveal considerable year-by-year species-specific fluctuations rather than a large-scale forest decline. Cases of obvious decline related to environmental factors are well circumscribed: (1) the deterioration of some coastal forests due to the action of polluted seaspray; (2) the deterioration of reforestation projects, especially conifers, mainly due to the poor ecological compatibility between species and site; and (3) the decline of deciduous oaks in southern Italy and of evergreen oaks in the Iberian peninsula apparently due to the interaction of climate stresses and pests and diseases. However, besides obvious deterioration, changes in environmental factors can provoke situations of more subtle stress. The most sensitive stands are Mediterranean conifer forests and mesophile forests of the Mediterranean-montane plane growing at the edges of the natural ecological distribution. Evergreen sclerophyllous forests appear less sensitive to variations in climatic parameters, since they can adapt quite well to both drought and the action of UV-B rays. Several experiments were carried out to test the sensitivity of Mediterranean forest species to air pollutants. Most of those experiments used seedlings of different species treated with pollutant concentrations too high to be realistic, so it is difficult to derive adequate information on the response of adult trees in field conditions. Ozone has been proved to cause foliar injury in a variety of native forest species in different Southern European countries, while the effects of other pollutants (e.g. nitrogen, sulphur, acidic deposition) are less obvious and likely to be very localized. In the case of ozone, visible symptoms were almost completely missed by large-scale surveys and-at the same time-non-visible symptoms are suspected to be even more widespread than the visible ones. Owing to this and to the complex relationships existing between species sensitivity, ozone exposure and doses, length of the vegetative periods, influence of climatic and edaphic condition on the tree's response, the impacted areas are yet to be identified. Therefore, the large-scale impact of air pollutants on the forests of Southern Europe remains largely unknown, until more specific investigations are carried out.
Keywords: forest conditions; Forest decline; Mediterranean Region; Ozone; pollution climate

Morpho-anatomical aterations in leaves of Fagus sylvatica L. and Quercus ilex L. in different environmental stress condition - Grossoni, P; Bussotti, F; Tani, C; Gravano, E (Chemosphere, 1998)
By means of anatomical and foliar structure observations, this paper examines the ecological behaviour of two different species of broadleaf (a mesophile one, beech, and a xerophile one, holm-oak), under different conditions of water supply. The purpose of this study was to evaluate their response in relation to possible climate changes. The results highlight certain similarities of behaviour (reduction of leaf surface, increased leaf thickness, increase of mechanical structures in xeric stands). The main difference between the two species lies in the tannins content, which increase in the epidermal cells (vacuoles and walls) only in beech trees in xeric conditions
Keywords: Fagus sylvatica; foliar structure; Quercus ilex; xeric conditions (voyant)

Crown status of holm oak (Quercus ilex L.) trees as related to phenology and environmental stress - Bussotti, F; Ferretti, M; Cozzi, A (Water, Air, & Soil …, 1995)
In order to study the possible interactions between air pollution and climate coaditions in Mediterranean evergream broadleaf species, since 1987 we have been monitoring the annual and infra-annual variations in crown density of Quercus ilex L. (holm oak) in a permanent sample plot. The behaviour of crown density has been compared with litterfall pattern and aging processes in leaves. The results of this study confirm the important impact of climate on crown condition in Meditea-raneeaa broadleaves, so that even the role of non- acute pollution can be disguised. Xeromorph adaptations in holm oak leaves are also a mechanism providing a greater protection against poltutants.
Keywords: abscission; crown condition; holm oak (voyant); leaves

The role of marine salt and surfactants in the decline of tyrrhenian coastal vegetation in Italy - Bussotti, F; Grossoni, P; Pantani, F (Annales des Sciences Forestières, 1995)
The decline of coastal vegetation is a phenomenon affecting some areas of the Mediterranean region and Australia; it is due to the presence of surfactants in marine aerosols, a consequence of sea pollution by detergents. This paper gives some observations made at various sites along the Tyrrhenian coast in Italy. The authors show that the presence of surfactants in the environment correlates with the presence of sea salt, and that the impact of surfactants on vegetation is local and occurs in association with strong sea winds. The study of the synergistic effect of surfactants and sea salt on the crowns of trees exposed to aerosols suggests that the surfactant can cause direct damage, while the absorption of sea salt is enhanced by the presence of the surfactant only when exposure to aerosol is prolonged, or if it is administered in very high concentrations.
Keywords: crown damage; leaf absorption; marine aerosol; NaCl; Pinus pinea L; surfactant

CROWN STRUCTURE MODIFICATIONS IN RELATION TO AIR-POLLUTION - Bussotti, F; BROGI, L; Grossoni, P; Cozzi, A; GELLINI, R (LANDSCAPE AND URBAN PLANNING, 1993)
Analysis of crown structure and crown modifications plays a role of primary importance in surveys of `new types of forest damage', since it is a decisive parameter in assessing the health status of a tree. Several forms of ramification alterations have been described in central and northern European species (Norway spruce, beech, Durmast oak, English oak, birch). This study examines the situation in Tuscany and offers a description of the alterations found in the main species typical of the Mediterranean region (Turkey oak, pubescent oak, holm oak, stone pine). The article discusses the potential impact of these alterations on the most typical forest formations, the ones which characterize the Tuscan landscape, and it describes the modifications already under way.
Keywords: crown structure; forest formations; Mediterranean

New types of damage to forest trees typical of the Mediterranean region - Clauser, F; GELLINI, R; Bussotti, F; Cenni, E; Bottacci, A (European Journal of Forest Pathology, 1989)
Since 1984 a new type of damage to the typical tree species growing in the mediterranean area has been observed. The pathological picture includes the typical features of “Waldsterben”. The new symptoms occurring in Pinus pinea, P. pinaster, P. halepensis and Quercus ilex are described.
Keywords: crown damage; damage; decline (voyant); foliage reduction